FINANCING-TO-VALUE (FTV) POLICY AND ITS IMPACT ON RESIDENTIAL PROPERTY PRICES IN INDONESIA - Imam Wahyudi Indrawan; Maya Puspa Rahman; Nurfatihah Ahmad Senusi (Journal of Islamic Monetary Economics and Finance, 2020)
Financing-to-value (FTV) policy is a macroprudential policy currently used by the central banks to maintain the stability of financial systems and prevent systemic risks. In Indonesia this is particularly the case in relation to financing of the property sector by Islamic financial institutions. This paper aims to analyse the impact of FTV policy on the residential property price index (RPPI) in Indonesia using a panel data analysis method. Indonesia is chosen in this study as it is one of the countries implementing FTV policy in its Islamic banking system. There are three important findings to be drawn from the study. First, FTV policy ratios significantly affect RPPI.